2016
DOI: 10.3389/fpls.2016.01616
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Distribution of Phytochemicals in the Leaves of 17 In vitro Cultured Hypericum spp. Adapted to Outdoor Conditions

Abstract: A plethora of plants belonging to the genus Hypericum have been investigated so far owing to the biological efficacies of pharmacologically important secondary metabolites produced by several Hypericum species. However, there is currently a dearth of information about the localization (accumulation) of these compounds in the plants in situ. In particular, the biosynthetic and ecological consequence of acclimatization of in vitro cultured Hypericum spp. to outdoor conditions is not fully known. Herein, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
(51 reference statements)
3
20
0
Order By: Relevance
“…Interestingly, a high content of pseudohypericin was detected in H. tomentosum in the present study, even though this species is characterized by the presence of only one or two dark glands on the leaf apex. This further upholds our earlier studies, [17,34] wherein pseudohypericin was also found to be localized in the dark glands located on the apex of H. tomentosum leaves. Our evaluation of the presence of hypericins further agrees with the previously published study by Ko suth et al (2011), [23] who studied the content of hypericin, pseudohypericin and emodin in in vitro grown seed-derived plants of 15 species of the genus Hypericum using HPLC-tandem mass spectrometry.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, a high content of pseudohypericin was detected in H. tomentosum in the present study, even though this species is characterized by the presence of only one or two dark glands on the leaf apex. This further upholds our earlier studies, [17,34] wherein pseudohypericin was also found to be localized in the dark glands located on the apex of H. tomentosum leaves. Our evaluation of the presence of hypericins further agrees with the previously published study by Ko suth et al (2011), [23] who studied the content of hypericin, pseudohypericin and emodin in in vitro grown seed-derived plants of 15 species of the genus Hypericum using HPLC-tandem mass spectrometry.…”
Section: Discussionsupporting
confidence: 92%
“…It was noted that the flavonoid rutin was not present in 7 Hypericum species, namely H. tetrapterum , H. rumeliacum , H. humifusum , H. tomentosum , H. pulchrum , H. androsaemum and H. kalmianum . The Hypericum species belonging to the section Ascyreia (i.e. H. stellatum , H. monogynum and H. kouytchense ), H. balearicum , H. perforatum , H. annulatum and H. bupleuroides contained rutin in all plant organs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7, 16]. In this paper, we tentatively identified new compounds present in the genus Hypericum and proposed that the anthraquinone skyrin is the key intermediate in hypericin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%